Peranan Guru Bimbingan dan Konseling Dalam Membina Interaksi Sosial Siswa di SMP Yapimda Jakarta - Ahiruddin, Ahiruddin; Rasjid, Harun (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
This study aims to determine the role of guidance and counseling teachers in fostering social interaction of students at Yapimda Middle School in Jakarta. The research method used in this study is a qualitative method with a descriptive approach. Namely the author looks for information and data as much as possible according to what it is at the time of the study conducted which is closely related to the role of teacher guidance and counseling in fostering student social interaction. The data and sources of data in this study were principals, guidance and counseling teachers and students of South Jakarta Yapimda Middle School, totaling 150 students as a population, consisting of classes VII, VIII and IX. The author assigns students from class VII, amounting to 35 students, and class VIII totaling 35 students to be used as research samples, so that the entire study sample was 70 students. The research instruments used in this study were questionnaires, interviews with school principals and guidance and counseling teachers and observations on the state of the school environment. Data analysis techniques are carried out by means of data collected through questionnaires, analyzed, summed according to the type, then analyzed, interpreted to be concluded as the results of the study. The conclusion of this study shows that